A public choice view on the climate and energy policy mix in the EU: How do the emissions trading scheme and support for renewable energies interact? - Erik Gawel; Sebastian Strunz; Paul Lehmann (Helmholtz-Zentrum für Umweltforschung (UFZ), 2013)
In this paper, we analyze the rationale for an energy policy mix when the European Emissions Trading scheme (ETS) is considered from a public choice perspective. That is, we argue that the economic textbook model of the ETS implausibly assumes 1) efficient policy design and 2) climate protection as the single objective of policy intervention. Contrary to these assumptions, we propose that the ETS originates from a political bargaining game within a context of multiple policy objectives. In particular, the emissions cap is negotiated between regulators and emitters with the emitters' abatement costs as crucial bargaining variable. This public choice view yields striking implications for an optimal policy mix comprising RES supporting policies. Whereas the textbook model implies that the ETS alone provides sufficient climate protection, our analysis suggests that support for renewable energies 1) contributes to a more effective ETS-design and 2) may even increase the overall efficiency of climate and energy policy if other externalities and policy objectives besides climate protection are considered. Thus, our analysis also shows that a public choice view not necessarily entails negative evaluations concerning efficiency and effectiveness of a policy mix.
Keywords: H23; Q42; Q48; Q58; 330